An Elegant Sense of Disgust. Visual Mapping of the Mannequin in Fashion Photography (Itinera, 2024)
The mannequin is a paradoxical figure, simultaneously captivating and disturbing. Within this ambiguity, the Surrealists explored the boundary between the animate and the inani- mate in search of that uncanniness that aligns with Freud’s concept of the Das Unheimli- che. This study investigates the peculiar sensation of disgust and repulsion provoked by this human simulacrum in surrealist fashion photography. The analysis is structured as a visual mapping of the mannequin, examining photographs published in Vogue between 1925 and 1945.The investigation reflects on the concept of disgust, here framed within Freud’s notion of the uncanny and interwoven with the Surrealist concept of convulsive beauty, tracing back to the Surrealists’ critique of capitalism, of which the mannequin becomes a vehicle. A comparison with Hans Bellmer’s explicitly disturbing Poupée highlights the polished perfection of the mannequins staged in fashion editorials by photographers such as Man Ray, Horst, Hoyningen-Huene, and Blumenfeld. Drawing upon theories of psychoanaly- sis, aesthetics, and art history, the study examines the factors that render these images disturbing: their artificiality, lifelessness, and resemblance to the human form. However, the Surrealist operation has a subversive edge: discomfort serves to reveal the circular relationship between art and consumerism.The visual trope of the mannequin, with its intrinsic duality of elegance and the abject, serves as a lens through which to examine this subtle undercurrent of unconscious disgust that permeates surrealist fashion photography, pushing the boundaries of artistic expres- sion and critique of modern society.
Keywords: Surrealism, Uncanny, Mannequin, Fashion Photography, Consumerism Critique